2020
DOI: 10.12688/wellcomeopenres.15556.2
|View full text |Cite
|
Sign up to set email alerts
|

Initiating a network to support engagement between health researchers and schools: recommendations from an international meeting of schools engagement practitioners held in Kilifi, Kenya

Abstract: Engagement between health researchers and local schools, or School Engagement, has become incorporated into the engagement strategies of many research institutions worldwide. Innovative initiatives have emerged within Wellcome Trust-funded African and Asian Programmes (APPs) and elsewhere, and continued funding from the Wellcome Trust and other funders is likely to catalyse further innovation. Engagement between scientists and schools is well-described in the scientific literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Youth advisory groups for health and health research engagement are an important model which serves to achieve the intrinsic goals of CE (Davies et al, 2020 ; Dickert & Sugarman, 2005 ; Pratt, 2019 ). The “intrinsic” goals are independent of whether the community/YAGHRE is ancillary to specific health research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Youth advisory groups for health and health research engagement are an important model which serves to achieve the intrinsic goals of CE (Davies et al, 2020 ; Dickert & Sugarman, 2005 ; Pratt, 2019 ). The “intrinsic” goals are independent of whether the community/YAGHRE is ancillary to specific health research.…”
Section: Discussionmentioning
confidence: 99%
“…New skills learnt by the students are an asset, some of which are likely to be retained for the future that included computer literacy and being able to carry out simple data analysis. Davies et al’s school engagement in Kenya has demonstrated the variety of impacts on students that ranged from learning new skills (such as photography and participatory video making) to pursuing a career in science (Davies, 2017 ; Davies et al, 2012 ). The skills and capacities developed by the YAGHRE members may serve their future career prospects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinctive video-making paths undertaken by the two groups reflected their differing circumstances, difficulties, priorities, and aspirations. The films proved to be effective tools for discussion and debate at all the events, underlining the advantages of participatory video approaches to engagement in health science research ( 30 ).…”
Section: Discussionmentioning
confidence: 99%